Implementation of Green Accounting as a Corporate Strategy in Supporting the Sustainable Development Goals (SDGs) - Ervina Waty (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the implementation of green accounting as a corporate strategy to support the achievement of the Sustainable Development Goals (SDGs). The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation in companies that have implemented sustainability reports. Data analysis was conducted using the Miles & Huberman model through data reduction, data presentation, and conclusion drawing. The results show that the implementation of green accounting in Indonesian companies is still partial and functions more as formal compliance than full integration into business strategy. Nevertheless, green accounting contributes significantly to the achievement of the SDGs, especially SDG 12 (Responsible Consumption and Production) and SDG 13 (Climate Action) through energy efficiency, waste management, and carbon emission reporting. The driving factors for the implementation of green accounting include regulations, investor pressure, and management awareness, while the obstacles faced are limited human resources, high investment costs, and the absence of standard operating procedures in Indonesia. This study confirms that green accounting can be a strategic instrument to support corporate sustainability and sustainable development.